POST‑IMPRESSIONISM AND THE CONSTRUCTION OF FRAGMENTED IDENTITY AND SUBJECTIVE RESISTANCE IN VERONICA ROTH’S DIVERGENT - Gopan, G. Iswarya (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study explores the inner conflicts and psychological struggles of the central character in Veronica Roth’s dystopian series Divergent. The debut novel, Divergent gained global recognition. Tris is a brave, selfless, strong willed sixteen year old protagonist. Divergent is becoming a massive young adult dystopian hit. Most of Roth’s works focus on dystopian, science fiction and young adult themes. Contemporary writers share similar themes of dystopian culture and science fiction fantasy elements. Science fiction writers often attempt to expand the new scientific and technical development in order to prognosticate the changes that happened in the technical world, which shock the readers’ sense of cultural propriety and expand their consciousness. The author elaborates the identity fragmentation of the character through the faction system followed by the people of Chicago, post-apocalyptic walled city. The narrative mainly focuses on the identity exploration and the attempt to escape from the wrath of powerful authority. It highlights the apocalyptic society and the inner suffering of people living in a desperate and voiceless situation under an authoritative government.